Metabolic Changes in Acute Rheumatic Fever - Karimov , Ma`rif Sh.; Khadjimatova, Iroda X. (Journal of Science in Medicine and Life, 2025)
Rheumatic fever, or acute rheumatic fever, is an inflammatory process that occurs as a complication of a streptococcal infection. This disease of the joints, mucous membranes, nervous system, or heart can become chronic and lead to heart defects and heart failure. Acute rheumatic fever (ARF) is a systemic inflammatory disease of connective tissue that occurs after streptococcal infection and is characterized by damage to the heart, joints, and nervous system. Despite advances in antibiotic prophylaxis, ARF remains a significant problem in developing countries. In recent years, particular attention has been paid to the study of metabolic changes in ARF, as they reflect the relationship between inflammation, energy metabolism, and disease outcome [1,6].